Vitamin D3 deficiency and MRONJ: insights from a Bi-Center Study in Argentina. A preliminary cross-sectional study - Gilligan, Gerardo; Leonardi, Nicolás; Garola, Federico; Piemonte, Eduardo; Panico, René (Journal of Oral Diagnosis, 2025)
Objetive: The aim of this study is to describe Vitamin D3 levels in patients diagnosed with MRONJ from two centers in Argentina. Methods: A cross-sectional study was conducted on patients from two Oral Medicine centers in Argentina. Patients diagnosed with Medication-related osteonecrosis of the jaw between 2016 and 2022 were included. Vitamin D3 levels were measured in plasma. The STROBE guidelines for reporting cross-sectional studies were followed. Results: The final sample consisted of 53 individuals. Among them, 60.4% had oncological-based diseases while 39.6% were diagnosed with osteoporosis. Oncological patients with Medication-related osteonecrosis showed lower vitamin D3 levels (23.9 ng/mL) compared to the osteoporosis group (32.9 ng/mL) (p=0.03). Conclusion: These preliminary findings described the levels of vitamin D3 in patients diagnosed with MRONJ, highlighting the relevance of investigating the role of vitamin D3 and its clinical outcomes in these patients. Future research in this area could provide valuable insights for a comprehensive understanding of this role.